Analisis Perkembangan Ekosistem Investasi Syariah di Negara-Negara Berpendapatan Menengah: Peluang dan Tantangan Pengembangannya - Aril Zumaedi; Risky Alfandi; Sarika Hannum; Evika Damayanti; Paisal Rahmat (AHKAM, 2026)
The development of the Islamic investment ecosystem in middle-income countries has become an important issue in the global financial industry because of its potential to increase financial inclusion and support sustainable development. Although various studies have discussed Islamic finance, studies that comprehensively analyze the development of the Islamic investment ecosystem along with its opportunities and challenges in middle-income countries remain limited. This study aims to analyze the development of the Islamic investment ecosystem, identify supporting factors and opportunities for its development, and examine the challenges faced. This study used a qualitative approach with a multi-case study design. Data were collected through documentation studies of policy documents, Islamic finance industry reports, regulator publications, reports from international institutions, and relevant scientific articles, then analyzed using thematic analysis through the processes of reduction, categorization, interpretation, and conclusion drawing. The results showed that the development of Islamic investment is marked by the growth of the Islamic capital market, increased sukuk issuance, the development of Islamic fintech, and regulatory strengthening. The growth of the Muslim population, increasing awareness of halal investment, advances in financial technology, and integration with sustainable finance are the main factors supporting this development. However, Islamic investment still faces challenges in the form of low Islamic financial literacy, limited infrastructure, lack of product innovation, regulatory differences, and digital security risks. The conclusion of this study affirms that strengthening the Islamic investment ecosystem in middle-income countries requires synergy among regulation, literacy, product innovation, digital infrastructure, and sustainable finance principles. The implications of this study provide theoretical contributions to the development of Islamic investment studies and practical contributions for regulators, Islamic financial institutions, and industry actors in formulating more inclusive, adaptive, and sustainable Islamic investment development strategies.